PRO ENVIRONMENTAL RECYCLING BEHAVIORS BEHAVIOR BASED ON EDUCATION LEVEL (STUDY CASE IN BENDUNGAN VILLAGE, INDONESIA) - Dafi Dinansyah Wiradimadja; Hisatsuna Mori; Tauny Akbari (Program Studi Teknik Lingkungan, Fakultas Teknik, Universitas Banten Jaya, 2024)
The countless debates and controversies that have taken place between communities, individuals, and organisations in Indonesia have contributed to the complexity of the country's environmental problems. These inconsistencies and contradictions may, in essence, be linked back to the factors that led to the environmental problems that we are experiencing and the possible remedies to those problems. People who live in Bendungan Village, Bogor Regency, Indonesia, are used as the sample's units of analysis when taking quantitative data. The goal of community sampling is to get first-hand information about things like trash, recycling, and eco-village activities that happen in the community. The research methodology utilised in this study is a mixed-methods approach. Based on the findings, it has been determined that there exists a discrepancy between the knowledge and actions of the individuals residing in Bendungan Village. This would be the case since their ideas are in direct antagonism to their behavior.The fact that people in the area have adequate information does not make them more likely to engage in environmentally conscious conduct; rather, it demonstrates that there are other factors outside education that influence people's behavior toward environmental sustainability.